Scalar Multiplication of Matrices Exercise with solution

By: Prof. Dr. Fazal Rehman Shamil | Last updated: December 26, 2024

[latex]
\[
\textbf{Q1: Multiply the Scalar 3 by the Matrix A, where:}
\]
\[
A = \begin{pmatrix} 1 & 2 \\ 3 & 4 \end{pmatrix}
\]
\[
\textbf{Solution:}
\]
\[
3 \cdot A = 3 \cdot \begin{pmatrix} 1 & 2 \\ 3 & 4 \end{pmatrix}
\]
\[
= \begin{pmatrix} 3 \cdot 1 & 3 \cdot 2 \\ 3 \cdot 3 & 3 \cdot 4 \end{pmatrix}
\]
\[
= \begin{pmatrix} 3 & 6 \\ 9 & 12 \end{pmatrix}
\]

\[
\textbf{Q2: Multiply the Scalar -2 by the Matrix B, where:}
\]
\[
B = \begin{pmatrix} 5 & -3 \\ 0 & 2 \end{pmatrix}
\]
\[
\textbf{Solution:}
\]
\[
-2 \cdot B = -2 \cdot \begin{pmatrix} 5 & -3 \\ 0 & 2 \end{pmatrix}
\]
\[
= \begin{pmatrix} -2 \cdot 5 & -2 \cdot (-3) \\ -2 \cdot 0 & -2 \cdot 2 \end{pmatrix}
\]
\[
= \begin{pmatrix} -10 & 6 \\ 0 & -4 \end{pmatrix}
\]

\[
\textbf{Q3: Multiply the Scalar 0.5 by the Matrix C, where:}
\]
\[
C = \begin{pmatrix} 8 & 6 \\ 4 & 2 \end{pmatrix}
\]
\[
\textbf{Solution:}
\]
\[
0.5 \cdot C = 0.5 \cdot \begin{pmatrix} 8 & 6 \\ 4 & 2 \end{pmatrix}
\]
\[
= \begin{pmatrix} 0.5 \cdot 8 & 0.5 \cdot 6 \\ 0.5 \cdot 4 & 0.5 \cdot 2 \end{pmatrix}
\]
\[
= \begin{pmatrix} 4 & 3 \\ 2 & 1 \end{pmatrix}
\]

\[
\textbf{Q4: Multiply the Scalar -1 by the Matrix D, where:}
\]
\[
D = \begin{pmatrix} 7 & 2 \\ -5 & 0 \end{pmatrix}
\]
\[
\textbf{Solution:}
\]
\[
-1 \cdot D = -1 \cdot \begin{pmatrix} 7 & 2 \\ -5 & 0 \end{pmatrix}
\]
\[
= \begin{pmatrix} -1 \cdot 7 & -1 \cdot 2 \\ -1 \cdot (-5) & -1 \cdot 0 \end{pmatrix}
\]
\[
= \begin{pmatrix} -7 & -2 \\ 5 & 0 \end{pmatrix}
\]

\[
\textbf{Q5: Multiply the Scalar 4 by the Zero Matrix E, where:}
\]
\[
E = \begin{pmatrix} 0 & 0 \\ 0 & 0 \end{pmatrix}
\]
\[
\textbf{Solution:}
\]
\[
4 \cdot E = 4 \cdot \begin{pmatrix} 0 & 0 \\ 0 & 0 \end{pmatrix}
\]
\[
= \begin{pmatrix} 4 \cdot 0 & 4 \cdot 0 \\ 4 \cdot 0 & 4 \cdot 0 \end{pmatrix}
\]
\[
= \begin{pmatrix} 0 & 0 \\ 0 & 0 \end{pmatrix}
\]

\[
\textbf{Q6: Multiply the Scalar 2 by the Identity Matrix F, where:}
\]
\[
F = \begin{pmatrix} 1 & 0 \\ 0 & 1 \end{pmatrix}
\]
\[
\textbf{Solution:}
\]
\[
2 \cdot F = 2 \cdot \begin{pmatrix} 1 & 0 \\ 0 & 1 \end{pmatrix}
\]
\[
= \begin{pmatrix} 2 \cdot 1 & 2 \cdot 0 \\ 2 \cdot 0 & 2 \cdot 1 \end{pmatrix}
\]
\[
= \begin{pmatrix} 2 & 0 \\ 0 & 2 \end{pmatrix}
\]